Dari Referensi menuju Kredibilitas: Bagaimana Praktik Bibliografi Membentuk Kualitas Wacana Akademik - Muhammad Rafii Athaillah; Ridho Ahmad Rasyid Waluyo; Agung Pranoto Kaditmaja (Jurnal Ilmiah Literasi Indonesia, 2026)
The credibility of scientific writing is a key indicator of research quality, influenced not only by argument strength but also by accurate bibliographic practices. This study aims to analyze the role of bibliography in enhancing academic credibility, identify common issues in reference management, and propose improvement strategies. Using a qualitative library research approach, data were collected from relevant academic literature and analyzed through content analysis. The findings show that proper bibliographic practices improve argument validity, academic integrity, and writing quality. However, issues such as inconsistent citation formats, use of non-credible sources, and mismatches between citations and references remain prevalent. The study concludes that the use of reference management tools and strong information literacy are essential to improve bibliographic practices and produce credible academic work.